Analysis of Age-Related Circular RNA Expression Profiles in Mesenchymal Stem Cells of Rat Bone Marrow - Sun, Hui; Sun, Yanan; Yu, Xiao; Gao, Xingyu; Wang, Huan; Zhang, Lin; Shi, Yingai; He, Xu (Frontiers in Genetics, 2021)
As multicellular organisms age, they undergo a reduction in tissue and organ function. The researchers have put forward a theory that stem cell aging is the main factor for declined function. In recent years, high-throughput sequencing technologies have evolved to identify circRNAs (circRNAs) in an increasing number of diseases, such as cancer and age-related diseases. It has been reported that circRNAs can compete with microRNA (miRNAs) to affect the stability or translation of target RNAs, and further regulate gene expression at the transcriptional level. However, the role of circRNAs in mesenchymal stem cells (MSCs) and its age-related aging mechanism have not been clarified. The purpose of this study was to explore and analyze the expression profiles of age-related circRNAs in MSCs. In this study, bone marrow MSCs were extracted from aged and young rats during the physiological aging and analyzed by high-throughput sequencing and bioinformatics. The reliability of high-throughput RNA sequencing was verified by quantitative real-time polymerase chain reaction. The most important circRNA functions and pathways were further selected by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomics (KEGG) analysis. Age-related circRNAs were found in the circrNA-miRNA-mRNA interaction network. The results of high-throughput sequencing showed that identified 4,229 circRNAs were involved in the age-related senescence of MSCs. Compared with the young group, there were 29 differentially expressed circRNAs, of which 4 were up-regulated and 25 were down-regulated. GO analysis covered three domains: biological process (BP), cellular component (CC) and molecular function (MF). The terms assigned to the BP domain were cellular metabolic process and cellular macromolecule metabolic process. The identified CC terms were intracellular, intracellular part, and the identified MF terms were binding and protein binding. The top five KEGG pathways were mitophagy-animal-rattus norvegicus, prostate cancer - rattus norvegicus, pathways in cancer - rattus norvegicus, lysosome - rattus norvegicus, and autophagy - animal - Rattus norvegicus. Altogether, CircRNAs may play a major role in the age-related MSC senescence. This study provides new mechanistic insights into MSC senescence, possibly leading to novel therapeutic strategies for age-related diseases.